Hepatitis A seroprevalence in homosexual and heterosexual men. Issue 5 (October 1994) - Nandwani, R; Caswell, S; Boag, F; Lawrence, A G; Coleman, J C
Abstract : OBJECTIVE--To determine the seroprevalence of hepatitis A antibodies in homosexual and heterosexual males attending a genitourinary medicine (GUM) clinic. DESIGN--Prospective study of male patients recruited from a GUM clinic during a 10 week period in 1993. SETTING--Central London outpatient GUM department at Chelsea and Westminster Hospital. SUBJECTS--255 patients were recruited, comprising 185 homosexual and 70 heterosexual males. Ninety two men were known to be HIV-positive, of whom 89 were homosexual. MAIN OUTCOME MEASURES--Serum samples were screened for both IgM and IgG antibodies to hepatitis A by enzyme linked immunoassay. Results were matched to an anonymously completed questionnaire. RESULTS--81 of the 255 subjects (31.8%) had been exposed to hepatitis A, two of whom were IgM positive. There were similar hepatitis A seroprevalence rates in homosexual (32.4%) and heterosexual men (30.0%). Although 48.1% of the homosexual men were known to be HIV-positive, compared with 4.3% of the heterosexuals. Hepatitis A seroprevalence remained comparable in both groups after patients with known HIV infection were excluded from the analysis. 11.4% of the heterosexual men admitted to oral-anal sexual contact compared with 62.2% of the homosexual men. This sexual practice was not associated with antibodies or a past history of hepatitis A exposure. CONCLUSIONS--There was no detectable difference in hepatitis A seroprevalence between male homosexual and heterosexual GUM clinic attenders, despite a much higher level of oral-anal sexual activity among the homosexual population.